Hormone Synchronization and Artificial Insemination as Breeding Efforts of Philemon buceroides to Prevent their Extinction - M. Yamin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Philemon buceroides is a bird that is very difficult to breed in captivity. This paper escribes the breeding efforts that have been carried out. The aims of the study are for knowing how to breed it in captivity and as a suggestion for conservation efforts in-situ and ex-situ. Efforts of breeding Philemon buceroides are conducted by supplying the Pregnant Mare Serum Godadotrophin (PMSG) hormone and the Estrogen hormone and artificial insemination for birds that are sexually mature at least one year old and physically healthy. The sample of Philemon buceroides in this study is birds that have been reared for at least 1 year to reduce stress. The sample of Philemon buceroides were acclimatized for 7 days in each bird cage according to the group. On the following day, the treatment group was superovulated to obtain more eggs than normal using PMSG hormone at a dose of 150 Im in 10 milli liters of ferologic Nacl / Kg BW once a day for three consecutive days. The control group was only given 10 milli liters of ferologic NaCl orally. The next day, synchronization of lust / Esterus was conducted using the Estrogen hormone at a dose of 150 Im in 10 milli liters of ferological NaCl orally once a day for three consecutive days. For male Philemon buceroides, sperm was collected. As a result, synchronization of the reproductive hormones of Pregnant Mare Serum Gonadotrophin (PMSG) and Estrogen to male and female Philemon buceroides greatly influenced the increase in ovulation of Philemon buceroides, however the eggs produced by the mother Philemon buceroides have not yet produced chicks. In addition, it is difficult to obtain the male sperm. From the three males, only one sperm pull out only 1 drop, the other two did not pull out any sperm.